2014
DOI: 10.1095/biolreprod.114.118083
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation Mouse Embryo Is a Target for Opioid Ligand-Receptor Signaling1

Abstract: Synchronization of preimplantation embryo development to blastocysts is one of the prerequisites for normal embryo implantation. While previous studies have ascribed an adverse effect to aberrant opioid signaling on embryo and fetal development, it has remained unclear whether the opioid system is operative in early pregnancy events. In the present study, employing multiple pharmacological and genetic approaches, we demonstrated that preimplantation embryos spanning the zygote to blastocyst express the opioid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…This coordination between endogenous opioid precursor synthesis by PC1/3 and degradation via MME plus the extra Bguidance^from Pcsk1n might help to create and maintain a low level of active opioid peptides that might be beneficial for uterine transformation prior to implantation. Indeed, our previous study demonstrated a similar phenomenon of a tightly regulated endogenous opioid system and the endocannabinoid system by the biosynthetic and metabolic pathway in the oviduct during preimplantation embryonic development (Chen et al 2014;). This notion is further confirmed by our observations obtained in pseudopregnant day 4 receptive versus day 6 refractory uteri and in the physiologically relevant delayed implantation mouse model.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…This coordination between endogenous opioid precursor synthesis by PC1/3 and degradation via MME plus the extra Bguidance^from Pcsk1n might help to create and maintain a low level of active opioid peptides that might be beneficial for uterine transformation prior to implantation. Indeed, our previous study demonstrated a similar phenomenon of a tightly regulated endogenous opioid system and the endocannabinoid system by the biosynthetic and metabolic pathway in the oviduct during preimplantation embryonic development (Chen et al 2014;). This notion is further confirmed by our observations obtained in pseudopregnant day 4 receptive versus day 6 refractory uteri and in the physiologically relevant delayed implantation mouse model.…”
Section: Discussionmentioning
confidence: 70%
“…Our previous study revealed that opioid receptor subtypes are dynamically expressed in preimplantation embryos (Chen et al 2014). With respect to the pathophysiological significance of opioid signaling in Pcsk1n (f, f') in ovariectomized mouse uteri treated with oil (Oil), estradiol-17β (E2), or progesterone (P4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, illicit use of opioids during pregnancy is often associated with adverse pregnancy outcomes, such as poor fetal growth, preterm delivery, and fetal death [11][12][13][14][15][16][17]. In this respect, our recent study revealed while the opioid signaling is functionally operative during preimplantation embryo development, an aberrantly activated opioid signaling by morphine can remarkably impair the normal preimplantation embryo development via inhibiting intracellular calcium mobilization [18]. However, it remained largely unexplored regarding the pathophysiological significance of opioid system on uterine functions at periimplantation.…”
Section: Introductionmentioning
confidence: 94%